AIToys : A Sustainability Approach - Ihamäki, Pirita; Heljakka, Katriina (United States, 2026)
Artificial Intelligence (AI) has increasingly entered the domain of play, transforming the affordances and functions of toys. AI-empowered toys are becoming prominent partners in lifelong and life-wide play, enhancing entertainment, education, and the development of empathy. Simultaneously, sustainability is often overlooked as an aspect of toy innovation. This study examines four existing and one speculated example of AIToys on the market through the lens of sustainability, aiming to understand how the three pillars of sustainability—ecological, ethical, and economic—are addressed in manufacturers' claims. The data consists of toy-maker descriptions and media articles, which were analyzed. The study's contribution is to examine and describe how AIToy development aligns with sustainability principles, a currently relevant area of research prompted by the ongoing transformation related to how Artificial Intelligence impacts human-toy relations. This study investigates AIToys through the lens of sustainability, emphasizing ecological, ethical, and economic considerations in their design. Unlike earlier generations of smart or connected toys, AIToys integrate advanced AI features that support continuous engagement beyond childhood. By analyzing manufacturer descriptions and media coverage of a selected sample of AIToys available in the 2025 online market, this research identifies key design directions that align with sustainability principles. The concept of AIToys, Artificial Intelligence-powered toys, has emerged as a distinct category within the broader domain of smart and connected play technologies. According to Heljakka and Ihamäki (2025), an AIToy is defined as a play object that integrates artificial intelligence to enable machine learning, interactivity, adaptability, and autonomy. These features distinguish AIToys from traditional toys and earlier generations of smart toys, which typically rely on pre-programmed responses or basic connectivity. Key capabilities of AIToys include adaptive learning, which ability to evolve behavior based on user interaction. Second one is natural language interaction, which is engaging users thought meaningful conversation. Third is emotional responsiveness, its recognizing and responding to affective cues. Fourth is physical motion embodied interaction through robotics or sensor-based movement. Aguilera et al. (2024) observe that contemporary AI-enhanced toys and robotic systems designed for children incorporate varying levels of artificial intelligence technologies—including machine learning, deep learning, natural language processing, and computer vision. These capabilities enable advanced functionalities such as facial and emotional recognition, voice-command-driven actions, personalized learning pathways, and support for multilingual interaction. In addition to the integration of AI systems, Costa, Périno and Ray-Kaeser (2018) emphasize the importance of the toy’s physical attributes in shaping the user experience. These include the presence of functional components such as cameras, speakers, and supplementary accessories designed to enhance play. Furthermore, the toys are characterized by their visual and tactile qualities—such as color schemes, textures, dimensions, and weight—as well as their capacity for movement and expressive gestures. While technological innovation is central to AIToy design, sustainability—ecological, ethical, and economic—is often underrepresented. At the same time, the importance of sustainability in toy design has grown significantly, especially in alignment with the United Nations Sustainable Development Goals1 (SDG 12, SDG 9, SDG 3). As Yadou et al. (2025) emphasize, toy design is not merely aesthetic or functional—it has a profound impact on child development, the environment, and society. Their study highlights that most toys on the market are plastic-based, short-lived, and environmentally harmful. Sustainable toy design requires the use of safe, biodegradable, and recyclable materials, as well as eco-friendly manufacturing processes.The research suggests that sustainable toy design must adopt a holistic approach, considering, user needs and developmental stages, material safety and environmental impact, energy-efficient production and waste management and product lifecycle and circular economy principles. For example, LEGO and Mattel are transitioning to bio-based and recycled plastics, while Hasbro has launched a toy recycling program. Additionally, 3D printing and modular design enable material-efficient and multifunctional toy production. Beyond the materiality of AIToys, questions arise about their longevity as interactive and relational technologies, which propose challenges regarding, e.g., e-waste and the socio-emotional attachment to non-human entities. This paper highlights these concerns through the lens of sustainability.
Keywords: AIToys, Sustainability Design, Toy Design, Communication Design
Artificial Intelligence and Social Computing 2025 : Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA, 26-30 July 2025